A Rare Case of Multiorgan Solid Cystic Lesion: Von Hippel Lindau Syndrome - An Institutional Experience - Vinothkumar B; Niveditha EN; Aravindan; Sonti Sulochana (Dr. Annil Mahajan, 2023)
Von Hippel-Lindau syndrome is a rare hereditary multisystemic tumour predisposition disorder, caused by a mutation in the VHL gene. The incidence is 1 in 39,000 individuals. Here we report a case of a 20-yearold male patient who presented with complaints of dull aching abdominal pain for 2 months. CT-abdomen shows a mixed solid cystic lesion in the right kidneys and right supra renal gland & benign serous cyst adenomatous in the pancreas. Right total adrenalectomy with enucleation of the right kidney was done. Histopathology and immunohistochemistry showed pheochromocytoma with clear cell renal carcinoma of the kidney.